Enhancing automotive cooling systems: composite fins and nanoparticles analysis in radiators - R. Ramesh Kumar; K. Karthik; P. V. Elumalai; R. Elumalai; Davannendran Chandran; E. Prakash; Nasim Hassin (Scientific Reports, 2024)
Abstract Composites are driving positive developments in the automobile sector. In this study investigated the use of composite fins in radiators using computational fluid dynamics (CFD) to analyze the fluid-flow phenomenon of nanoparticles and hydrogen gas. Our world is rapidly transforming, and new technologies are leading to positive revolutions in today’s society. In this study successfully analyzed the entire thermal simulation processes of the radiator, as well as the composite fin arrangements with stress efficiency rates. The study examined the velocity path, pressure variations, and temperature distribution in the radiator setup. As found that nanoparticles and composite fins provide superior thermal heat rates and results. The combination of an aluminum radiator and composite fins in future models will support the control of cooling systems in automotive applications. The final investigation statement showed a 12% improvement with nanoparticles, where the velocity was 1.61 m/s and the radiator system’s pressure volume was 2.44 MPa. In the fin condition, the stress rate was 3.60 N/mm2.